Design of robot finger based on flexible tactile sensor. (4th October 2019) - Tang, Zhijie; Wang, Zhen; Lu, Jiaqi; Ma, Gaoqian
In this article, a flexible tactile sensor that made of conductive silicone rubber for dexterous robot hand is designed. The tactile sensor is made up of four microsensors. The maximum gripping force is simulated when the degree of a robot finger joint is 138. Meanwhile, a control system to analyze the creep and hysteresis characteristics and a processing system of the tactile sensor is designed. We also demonstrated an experiment for the application of robot grasp object, showing the finger's flexibility and sensitivity. Then the feedback data is sent to control system to provide precise grasp action changes for the robot hand.